Scriptura Translata, Semper Transferenda: An English Version of Theodore Beza's Syncretistic Abraham sacrifiant - McCutcheon, Robert (Renaissance and reformation, 2025)
Theodore Beza's 1550 Abraham sacrifiant continues a rich tradition of translation and exegesis of the Akedah in the vibrant context of the humanist Reformation. Beza translates not so much from one language to another, since he takes the Olivetan Bible's text of Genesis 22 for the argument of his play, but rather fuses two cultures and genres, Biblical narrative and Greek tragedy. His choice entails a crucial tension: a drama of redemption cannot be tragic. In fact, Beza incorporates comic elements from both medieval and classical sources in his work. Nonetheless, his work puts in play Calvinist themes such as saving faith and predestination. A modern translation should be faithful both to Beza's adaptation of classical forms, such as stichomythia and choral odes, and to his expression of reformed doctrine, in the spirit of Arthur Golding's near-contemporary English version of 1575. Like Golding's translation, mine will inevitably adapt form and content to each other, with luck conveying Beza's literary theology in the process.